Shared decision making: A dual‐layer model to tackling multimorbidity in primary care - Ng, Chirk Jenn; Lee, Yew Kong; Abdullah, Adina; Abu Bakar, Ahmad Ihsan; Abdul Malik, Tun Firzara; Tiew, Han Wei (Wiley, 2019)
It is common for primary care providers (PCPs) to manage complex multimorbidity. When caring for patients with multimorbidity, PCPs face challenges to tackle several issues within a short consultation in order to address patients' complex needs. Furthermore, some PCPs may lack access to a multidisciplinary team and need to manage multimorbidity within the confine of a PCP-patient partnership only. Instead of attempting to address multiple health issues within a single consultation, it would be more feasible and time effective for PCPs and patients to jointly prioritize the health issue to focus on. Using the Malaysian primary care setting as a case study, a dual-layer-shared decision-making approach is proposed whereby PCPs and patients make decisions on which disease(s) (layer 1) and treatment(s) (layer 2) to prioritize. This dual-layer model aims to address the challenges of short consultation time and limited healthcare resources by encouraging PCPs and patients to discuss, negotiate, and agree on the decision during the consultation to ensure patients' health needs are addressed. © 2019 John Wiley & Sons, Ltd.